Dipole-field distributions in complex magnetic materials - Blundell, S (2009)
The probability distribution of local magnetic field values experienced by implanted muons, given no prior information on the muon site, is calculated for various arrangements of magnetic dipoles commonly found in magnetic materials. Such distributions are useful for interpreting μSR data on complex magnetic systems such as molecular magnets where there are many possible muon sites. © 2009 Elsevier B.V. All rights reserved.